Research on perception bias of implementation benefits of urban intelligent transportation system based on big data - Hu, Xiao; Deng, Zhenghua (EURASIP journal on wireless communications and networking, 2019)
Providing convenient and comfortable transportation services for residents is an important part of urban construction, in which the intelligent transportation system (ITS) plays an important role. This study used the big data of urban public transportation in China and the evaluation of ITS in tourism e-commerce website to compare travelers’ perception of urban intelligent transportation with the objective effects of ITS and analyzed the factors that affect the perception bias of urban residents about ITS. The conclusions are as follows: (1) there are regional differences in travelers’ perception of ITS. The traveler’s evaluation of ITS in the cities of East China is best in China, followed by cities in the central and southwestern regions. (2) The perception bias of urban residents from ITS is generally affected by the density of road network and travel radius. The influencing factors of perception bias are obviously different between provincial capital cities and non-provincial capital cities. (3) The use of digital maps, navigation, and intelligent road conditions in the travel process can improve travelers’ evaluation of ITS.